Cognitive-motivational dimmensions and self-regulated learning - Valle Arias, Antonio (1996)
This paper discusses schoollearning from a cognitive-motivational perspective. A number of relevant ideas are highlighted as relevant to undersrand the cognitive-motivational factors that influence school learning.